A scoping review : Potential nutraceutical values of bioactive compounds and antioxidant activity in durian seed – An exotic tropical plant - Aisyah, Siti; Harioputro, Dhani Redhono; Nurwati, Ida (Indonesian Nutrition Association, 2025)
Background: Durian is a tropical fruit with a unique flavour and intense aroma. All parts of durian are reported to have many health benefits, especially the seeds. The seeds are known to have higher antioxidant activity and phytochemical compound than the pulp. Durian seeds are food waste that has the potential to be reused in the food and health industry. Objective: This article provides information on the presence of bioactive compounds, antioxidant activity, and the potential use of durian seeds as therapeutic agents. Methods: The study used a scoping review with four databases: Google Scholar, PubMed, DOAJ, and ScienceDirect. Scoping is needed to complete the article, summarize scientific data, and as a future reference regarding the nutraceutical potential of durian seeds. Results: A total of 6 articles were reviewed based on the screening results. The bioactive compounds found in these articles are phenolics, flavonoids, α-tocopherol, terpenoids, saponins, anthraquinones, and several flavonoid classes such as catechin, rutin, isoquercitrin, quercitrin. Total phenolic content (TPC) and antioxidant activity were highest in the Chanee durian seed cultivar compared to the Monthong type and various other cultivars from several countries. Conclusion: Durian seeds as food waste seem to have potential as a nutraceutical. Known as food waste that is rarely utilized, based on several studies, durian seeds have several benefits, one of which is to overcome various diseases. Further research needs to be done to prove that durian seeds can be helpful in the food industry as well as in pharmaceutical and cosmetic applications.